SOCIAL PHYSIQUE ANXIETY, DISTURBED EATING ATTITUDES AND BEHAVIORS, AND PERCEIVED PRESSURE FOR THIN BODY IN COMPETITIVE RHYTHMIC AND AEROBIC GYMNASTS - Fotini Venetsanou; Christina Ioannidou (University of Ljubljana Press (Založba Univerze v Ljubljani), 2019)
This study investigated social physique anxiety (SPA), disturbed eating attitudes and behaviors (DEAB), and perceived pressure for thin body by the "significant others" (coach, parents, peers, experts) in 41 female rhythmic gymnastics (RG) and 49 aerobic gymnastics (AG) athletes at competitive level. Moreover, the potential impact of gymnasts' BMI was examined and controlled. Results showed that BMI associated with gymnasts' SPA, DEAB and perceived pressure, so its effect was controlled. There were no significant differences between RG and AG regarding SPA and DEAB, whereas AG athletes had higher parental pressure for thin body than RG athletes. When RG and AG data were merged, a high percentage (40%) of gymnasts presenting DEAB was revealed. Gymnasts with DEAB had significantly higher SPA and perceived pressure for thin body than those with normal eating attitudes and behaviors. These results underline the need for interventions involving "significant others" and aiming at DEAB prevention in female gymnasts.